Factores de riesgo de mortalidad en obstrucción intestinal por vólvulo de sigmoides, Hospital Belén de Trujillo, 2017 – 2019 - Ordoñez Sullon, Cristhiam Medin (2019)
Intestinal obstruction is one of the most frequent causes of acute surgical abdomen in emergency, sigmoid volvulus is a common cause of intestinal obstruction and is the third cause of large bowel obstruction in the world. Objective: To identify the risk factors for mortality in intestinal obstruction due to sigmoid volvulus in patients at Hospital Belén de Trujillo. Material and Method: Descriptive, analytical and of the case and control type, carried out in the General Surgery service of the Belén de Trujillo Hospital, during the period 2017 - 2019, working with all the cases presented during the established period, for the controls The 2 to 1 relationship was used according to the cases presented. Results: Age, sex, origin, length of illness, ASA, surgical technique, lactate level, pH and base deficit are risk factors for mortality.